RNase1 can modulate gut microbiota and metabolome after Aeromonas hydrophila infection in blunt snout bream. (20th May 2021) - Geng, Ruijing; Liu, Han; Tan, Kianann; Wang, Zhiqiang; Wang, Weimin
Summary: Pancreatic ribonuclease (RNase1) of Megalobrama amblycephala exhibits both antimicrobial and digestive activity. The gut microbiome improve the digestion and metabolic capacity and enhance the functioning of the immune system of the host against pathogenic bacteria. In this study, we aimed to assess the protective effect of RNase1 on Aeromonas hydrophila‐ induced inflammation and intestinal microbial metabolism. Megalobrama amblycephala were randomly divided into three groups: control (injected PBS), infection ( A. hydrophila‐ injected), and treatment group (RNase1 pretreatment 24 h before the A. hydrophila injection). The morphological symptoms were significantly alleviated by RNase1. RNase1 reshaped the perturbed gut microbiota by upregulating Proteobacteria and Vibrio richness and downregulating Firmicutes, Chlamydiae, Bacillus, and Gemmobacter richness. The lysophosphatidylcholine, (±) 17 HETE, D‐ (+) ‐cellobiose, and PC (20:5) in the treatment group were restored by RNase 1 protein treatment to the level of the control group. In the treatment group, phospholipid metabolism, fatty acid metabolism, glucose metabolism and lipid metabolism were different from the control and infection groups. The proinflammatory factors concentration in intestinal samples significantly increased after A. hydrophila infection. Our results revealed that RNase1 plays an important role in resistance to pathogen invasion, reducing inflammation, and improving intestinal function, thus inhibiting the occurrence of disease.